2004
DOI: 10.1097/00004010-200401000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Patient's Mammogram Experience

Abstract: This study overviews an operational blueprint that diagrams the activities and interactions of all participants in a typical screening mammography appointment in a large medical center. The blueprint is constructed from multiple sources of data collected from mammography patients, service providers in the radiology department, and medical records. The benefits from using patient perspectives, the insights gained from the blueprint development process, and the value of the resulting screening mammography appoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…32 Primary care physician recommendation of screening has been shown to be one of the strongest predictors of receipts of screening. [107][108][109][110] Better communication between primary care providers and specialist mental health services might improve prescribing for mental and physical ill health. 75,111 However, in a trial of an integrated model of care for older people, the intervention helped with access but did not produce any significant treatment effects for depression or anxiety.…”
Section: Figmentioning
confidence: 99%
“…32 Primary care physician recommendation of screening has been shown to be one of the strongest predictors of receipts of screening. [107][108][109][110] Better communication between primary care providers and specialist mental health services might improve prescribing for mental and physical ill health. 75,111 However, in a trial of an integrated model of care for older people, the intervention helped with access but did not produce any significant treatment effects for depression or anxiety.…”
Section: Figmentioning
confidence: 99%
“…The process of service blueprint is: identifying process, isolating fail points, establishing timeframe, and analyzing profitability. Dodendorf et al, (2004) developed a blueprint of the mammography service in the USA. The blueprint shown in Figure 1 maps out the experience of the patient in making a mammography appointment until the last stage, which is getting the result.…”
Section: Service Blueprintmentioning
confidence: 99%
“…Source: Dodendorf et al (2004) Creating blueprint requires several methods for data collection such as patient Advances in Economics, Business and Management Research,volume 40 scripts, patient pathways, field notes, paper/electronic trails of referral, diagnosis, test results and communication, and chart audits. The process of collecting the data is quite long and expensive because it requires several people to collect the data.…”
Section: Service Blueprintmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, they are likely to expect to end their screening process finding nothing wrong. Indeed, Dodendorf et al (2004) interviewed mammography patients to create a blueprint of the mammography appointment and found that the patients' group scripts did not include a contingency should abnormal results be found. Patients awaiting diagnostic mammograms, on the other hand, are more likely to view themselves in a "sick" role.…”
Section: Moderating Role Of Testing Stagementioning
confidence: 99%